C-Type Natriuretic Peptide Plays an Anti-Inflammatory Role in Rat Epididymitis Induced by UPEC - Mei, Chunlei; Kang, Yafei; Zhang, Chenlu; He, Chunyu; Liao, Aihua; Huang, Donghui (Frontiers in Cellular and Infection Microbiology, 2021)
Human epididymitis is mainly caused by retrograde urinary tract infection with uropathogenic Escherichia coli（UPEC）. This disease is an important factor (accounting for 20-30%) causing male infertility. C-type natriuretic peptide (CNP), a protein composed of 22 amino acids, is expressed predominately in the epididymis. It plays an immunoregulatory role in respiratory and cardiovascular systems. However, the role of CNP in acute epididymitis is unclear. First, we established an acute caput epididymitis model in rats with UPEC and treated them with CNP. H&E staining (HE), quantitative polymerase chain reaction (qPCR), Enzyme Linked Immunosorbent Assay (ELISA) and western blot were used to measure inflammatory damage. RAN-Seq transcriptome technology revealed signaling pathways. Second, the turbidity and activity of UPEC were assessed using a microplate reader as well as the amount of UPEC by agar plates after incubation with CNP. Third, macrophages in caput epididymis were tested by Immunohistochemistry (IHC). The macrophage line RAW264.7 was cocultured with Lipopolysaccharide (LPS) or CNP, then proinflammatory factors were measured. Cell proliferation activity was assessed with a CCK–8 kit. Finally, after we cultured macrophages with CNP alone or in conjunction with 8-Br-cGMP (cyclic guanosinc monophosphate (cGMP) analog) and KT5823 (Protein kinases G (PKG) inhibitor), the levels of Nuclear factor-k-gene binding (NF-kB) and downstream proinflammatory factors were detected. We found that the damage of caput epididymis was alleviated significantly and proinflammatory factors decreased after treatment with CNP. In vivo, the activity and numbers of bacteria decreased after CNP intervention, and the invasion of macrophages is less. CNP repressed the activity and the proinflammatory factors in macrophages, NF-kB may be inhibited by CNP and/or 8-Br-cGMP but be upregulated by PKG. Finally, we can draw a conclusion that CNP alleviates the acute epididymitis injury through inhibiting the UPEC and reducing NF-kB in macrophages through the cGMP/PKG signaling pathway. CNP may become a potential treatment for epididymitis. However, CNP alone may not be a sufficient enough treatment for urinary tract infection. A combination of CNP with antibiotics may be necessary. This research would open up the possibility of using a lower dose of antibiotics when combined with CNP.